IS AMNIOINFUSION EFFECTIVE ENOUGH TO REDUCE PERINATAL MORTALITY? - Ajmal, Wajiha; Zaki, Adil; Khan, Aliya; Bashir, Uzma; ., Naveeda; ., Pashtana; Minhas, Zakia (Journal of Postgraduate Medical Institute, 2011)
Objective: To assess the effects of amnioinfusion for meconium stained liquor on reducing perinatal death. Material and Methods: This case control study was conducted in Kalsoom Maternity hospital, Peshawar on singleton pregnancies with cephalic presentation, >37 weeks gestation and meconium stained liquor at admission or during labor, randomized in two groups. Group 1 (study group) received amnioinfusion (normal saline 500mls at room temperature) over a period of 30 minutes at a rate of 10-20 mls/min. Group 2 (control group) did not receive such treatment. Fetal heart monitoring at every 10-15 minutes along with progress of labour plotted on a partogram was recorded. Results: Out of 82 cases, 1 breech and 2 premature were excluded so 79 were left for the study. All were with cephalic presentation and gestation >37 weeks in 73.41% cases and postdates in 26.5% cases. In Group 1 (n=52), 36 (69.2%) had normal vaginal delivery (NVD), 4(7.7%) had outlet forceps delivery, 12(23.1%) had vacuum vaginal delivery and cesarean section rate was 0%. Two (3.8%) newborns were referred to nursery with 1 (1.9%) early neonatal death. In Group 2 (n=27), 6 (22.2%) had NVD, 11(40.7%) delivered with outlet forceps, 10(37.1%) had vacuum vaginal delivery and no cesarean section. Twelve (44.4%) babies were referred to nursery with 2 (7.4%) early neonatal deaths. Conclusion: Amnioinfusion is associated with improvements in perinatal outcome, particularly in settings where facilities for fetal surveillance are limited. The technique appears to be safe, simple and economical.